Behavior problems and placement change in a national child welfare sample: a prospective study - Aarons, Gregory A; James, Sigrid; Monn, Amy R; Raghavan, Ramesh; Wells, Rebecca S; Leslie, Laurel K (Journal of the American Academy of Child and Adolescent Psychiatry, 2010)
There is ongoing debate regarding the impact of youth behavior problems on placement change in child welfare compared to the impact of placement change on behavior problems. Existing studies provide support for both perspectives. The purpose of this study was to prospectively examine the relations of behavior problems and placement change in a nationally representative sample of youths in the National Survey of Child and Adolescent Well-Being. The sample consisted of 500 youths in the child welfare system with out-of-home placements over the course of the National Survey of Child and Adolescent Well-Being study. We used a prospective cross-lag design and path analysis to examine reciprocal effects of behavior problems and placement change, testing an overall model and models examining effects of age and gender. In the overall model, out of a total of eight path coefficients, behavior problems significantly predicted placement changes for three paths and placement change predicted behavior problems for one path. Internalizing and externalizing behavior problems at baseline predicted placement change between baseline and 18 months. Behavior problems at an older age and externalizing behavior at 18 months appear to confer an increased risk of placement change. Of note, among female subjects, placement changes later in the study predicted subsequent internalizing and externalizing behavior problems. In keeping with recommendations from a number of professional bodies, we suggest that initial and ongoing screening for internalizing and externalizing behavior problems be instituted as part of standard practice for youths entering or transitioning in the child welfare system.